Lithium metal negative electrode with volume expansion self-adaptability as well as preparation method and application of lithium metal negative electrode
By growing sulfides on the carbon felt and compounding with lithium metal, the problem of volume expansion and uneven deposition of lithium metal negative electrode during circulation is solved, high mechanical performance and cycle stability are achieved, the preparation process is simplified and the battery is improved energy density.
Patent Information
- Application Number
- CN202411339947.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The volume expansion of the lithium metal negative electrode during the circulation process leads to uncontrollable growth of lithium dendrites and the rupture of the intermediate phase of the solid electrolyte, affecting the battery capacity and safety. The prior art methods are complex and costly, affecting the energy density.
Sulfide is grown on commercial carbon felts and combined with lithium metal through rolling pressure to form a lithium metal negative electrode with high mechanical properties, which slows down the uneven deposition of lithium metal and dendrites and improves the adaptive ability of volume expansion.
The uniform deposition and high mechanical properties of lithium metal negative electrode are achieved, the volume expansion is reduced, the preparation process is simplified, and the cycle stability and energy density of the battery are improved.
Smart Images

Figure CN119208542A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal batteries, and in particular relates to a lithium metal negative electrode with volume expansion adaptability, and a preparation method and application thereof. Background Art
[0002] Lithium (Li) metal anodes are recognized as the ultimate anode choice for achieving high energy density battery systems due to their lowest electrochemical potential and highest theoretical specific capacity. However, host-free lithium metal anodes usually experience unacceptable volume expansion, which further promotes uncontrollable lithium dendrite growth and rupture of the solid electrolyte interphase (SEI), resulting in rapid capacity decline and potential short circuit risks. In addition, the volume expansion of lithium metal anodes during cycling will also lead to a continuous increase in electrode thickness and interfacial stress between the electrode and the separator, resulting in battery bulging and structural failure. In particular, flexible batteries cannot use rigid structural parts to limit expansion, and the consequences of these volume expansions become more significant in flexible lithium metal batteries.
[0003] Several methods for preparing lithium metal anodes with volume expansion adaptability are disclosed in the prior art, as follows: First, an emerging and reasonable strategy for designing composite anodes to regulate the deposition / dissolution of internal Li. The adaptive pressure is generated by the elastic polymer filled inside the conductive body, which exceeds the yield strength of Li and can limit the growth of internal Li. At the same time, the electron path persists under pressure, so that Li forms a smooth and highly utilized morphology, reducing the formation of dead Li. Under actual conditions, the pressure-adaptive composite anode has a capacity retention rate of 80% after 160 cycles, while the planar Li anode can be cycled 60 times in actual applications. Second, a team has developed a roll-to-roll method to prepare a lithium composite anode with zero volume expansion, which can significantly improve the energy density and bendable mechanical properties of lithium metal batteries. The anode has a sandwich structure: including an upper electronic insulating layer, a bottom lithium-philic layer, and a porous layer in the middle that absorbs volume expansion. The author further verified the excellent flexibility, energy density, and cycle retention of the lithium metal battery by matching NCM and LCO positive electrodes. Third, predecessors explored the effect of external pressure on the plating and stripping behavior of lithium metal batteries and proposed a two-stage cycling process to achieve soft-pack battery expansion control below 10%, which is comparable to existing lithium-ion batteries. Through a hybrid design, the self-generated pressure was monitored and quantified and correlated with the observed charge and discharge process. The results show that the volume expansion of lithium metal soft-pack batteries during cycling can be effectively suppressed through appropriate external pressure and balanced battery design.
[0004] However, this method has problems such as complex process and high cost. The added supporting materials are heavy, which seriously affects the energy density of lithium metal. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a lithium metal negative electrode with volume expansion adaptability and a preparation method and application thereof, wherein one or more sulfides are grown on commercial carbon felt, and the lithium metal is modified by simple rolling to obtain a lithium metal electrode. The strength of this electrode is higher than that of lithium metal and has good mechanical properties; the introduction of carbon fibers on which sulfides are grown slows down the uneven deposition and dendrite growth of lithium metal; the introduction of carbon felt with good macroscopic strength improves the volume expansion adaptability of the battery.
[0006] To achieve the above object, the present invention provides a method for preparing a lithium metal negative electrode with volume expansion adaptability, comprising the following steps:
[0007] (1) immersing the carbon felt in a mixed solution of a metal salt and a sulfur source, performing a hydrothermal treatment, and cooling to obtain a pretreated carbon felt;
[0008] (2) The pretreated carbon felt in step (1) is rinsed with deionized water and dried to obtain sulfide carbon felt;
[0009] (3) taking a lithium foil and two pieces of the carbon sulfide felt described in step (2), covering the carbon sulfide felt above and below the lithium foil respectively, and rolling to obtain a carbon sulfide felt and lithium metal composite;
[0010] (4) The carbon sulfide felt and the lithium metal complex described in step (3) are heated to react to obtain a lithium metal negative electrode.
[0011] Preferably, in the mixed solution of the metal salt and the sulfur source in step (1), the concentration of the sulfur source is 0.01-2 mol / L, the metal salt is one or more of zinc salt, molybdenum salt or tin salt, and the sulfur source is thiourea and / or thioacetamide. Depending on the sulfide to be grown, a suitable metal salt precursor and reaction temperature are selected, zinc salt is selected for the growth of zinc sulfide, molybdenum salt is selected for the growth of molybdenum sulfide, and tin salt is selected for the growth of tin sulfide. The concentration of the metal salt precursor will affect the density of the sulfide grown on the carbon felt.
[0012] Further preferably, the concentration of the zinc salt is 0.01 to 1 mol / L, and the zinc salt is zinc acetate or zinc chloride, the concentration of the molybdenum salt is 0.01 to 1 mol / L, and the molybdenum salt is ammonium molybdate or molybdenum chloride, and the concentration of the tin salt is 0.01 to 1 mol / L, and the tin salt is tin chloride.
[0013] Preferably, the weight density of the carbon felt in step (1) is 5 to 30 g / m 2 .
[0014] Preferably, the temperature of the hydrothermal treatment in step (1) is 130 to 200° C., and the time of the hydrothermal treatment is 5 to 48 hours.
[0015] Preferably, the drying temperature in step (2) is 50-100° C., and the drying time is 10-16 hours.
[0016] Preferably, the thickness of the lithium foil in step (3) is 5 to 200 μm; the rolling pressure in step (3) is 0.5 to 10 T, and the number of rolling is 1 to 2 times; the thickness of the carbon sulfide felt and lithium metal composite in step (3) is 30 to 500 μm. The carbon sulfide felt and lithium metal are tightly composited by multiple rolling, and the thickness of the carbon sulfide felt and lithium metal composite can depend on the desired thickness.
[0017] Preferably, the temperature of the heating reaction in step (4) is 100 to 180° C., and the heating reaction time is 1 to 48 hours. The lithium metal and the sulfide are fully reacted, which is beneficial to improving the subsequent battery performance.
[0018] The invention also provides a lithium metal negative electrode prepared by the preparation method.
[0019] The present invention also provides the use of the lithium metal negative electrode in preparing a lithium metal battery with adaptive volume expansion performance.
[0020] Compared with the prior art, the present invention has the following advantages and technical effects:
[0021] The present invention first grows a suitable sulfide (zinc sulfide, tin sulfide, etc.) on carbon fiber, and then composites lithium metal and carbon sulfide felt by rolling to serve as a lithium metal negative electrode.
[0022] 1. The problem of uneven deposition of lithium metal during the cycle and easy formation of lithium dendrites is solved. Sulfide sites are introduced to induce uniform deposition of lithium metal and reduce uneven deposition and dendrite growth.
[0023] 2. The high quality or high thickness of the existing three-dimensional materials to modify the lithium metal negative electrode leads to low battery energy density. The use of low-density carbon fiber to modify the lithium metal reduces the impact on its energy density.
[0024] 3. The modification process of lithium metal is complicated, and it needs to be modified one by one through multiple different steps. The complicated preparation process is not conducive to practical application and industrial large-scale production. The present invention first modifies the carbon felt, which is a simple and easy process, and then uses the carbon felt grown with sulfide to modify the lithium metal. The lithium metal modification process is relatively simple, and the whole process has low environmental requirements.
[0025] 4. In response to the volume expansion problem of lithium metal batteries, carbon fibers with better macroscopic strength play a supporting role, slowing down the volume expansion and improving the adaptability of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The scanning electron microscope images of the sulfide carbon felt prepared in Example 1, wherein a is an electron microscope image with a scale of 200 μm, and b is an electron microscope image with a scale of 300 μm;
[0028] Figure 2 The scanning electron microscope images of the lithium metal negative electrode prepared by the present invention, wherein a is an electron microscope image of the upper surface of the lithium metal negative electrode with a thickness of 100 μm, and the scale is 100 μm, b is an electron microscope image of the cross section of the lithium metal negative electrode with a thickness of 100 μm, and the scale is 100 μm, c is an electron microscope image of the upper surface of the lithium metal negative electrode with a thickness of 170 μm, and the scale is 500 μm, and d is an electron microscope image of the cross section of the lithium metal negative electrode with a thickness of 170 μm, and the scale is 400 μm;
[0029] Figure 3 The X-ray diffraction pattern of the sulfide grown on the sulfide felt prepared in Example 1;
[0030] Figure 4 The tensile stress-strain curves of the lithium metal negative electrode prepared in Example 1 and the lithium foil used in Example 1;
[0031] Figure 5 Cycling performance of button symmetrical batteries assembled with the lithium metal negative electrode prepared in Example 1 and the lithium foil used in Example 1;
[0032] Figure 6 The thickness variation trend diagram of each discharge cycle in the soft-pack battery assembled with the lithium metal negative electrode prepared in Example 1 and the lithium foil used in Example 1;
[0033] Figure 7 This is a schematic diagram of the cross-sectional structure of the lithium metal negative electrode prepared in Example 1. DETAILED DESCRIPTION
[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0039] The source of the material used in the present invention: weight density is 5-30g / m 2 The commercial carbon felt was purchased from Changzhou Hualike New Materials Co., Ltd.
[0040] Example 1
[0041] (1) In a hydrothermal kettle, a mixture of 10 g / m 2 The commercial carbon felt was immersed in a mixed solution of metal salt and thiourea (the metal salt was a mixture of zinc acetate, ammonium molybdate and tin chloride, wherein the concentration of zinc acetate was 0.06 mol / L, the concentration of ammonium molybdate was 0.06 mol / L, the concentration of tin chloride was 0.06 mol / L, and the concentration of thiourea was 0.2 mol / L), and hydrothermally treated at 180°C for 16 h, cooled to room temperature, opened the hydrothermal reactor, and took out the pretreated carbon felt;
[0042] (2) The pretreated carbon felt was rinsed with deionized water and dried at 80° C. for 12 h to obtain sulfide carbon felt;
[0043] (3) taking a lithium foil with a thickness of 50 μm and two carbon sulfide felts, covering the carbon sulfide felts on the upper and lower sides of the lithium foils respectively, and rolling them once with 2T to obtain a carbon sulfide felt and lithium metal composite with a thickness of 100 μm;
[0044] (4) The carbon sulfide felt and lithium metal complex were heated at 160°C for 12 h to obtain a lithium metal negative electrode (such as Figure 7 shown).
[0045] like Figure 1 A and Figure 1 As shown in b, it is a scanning electron microscope image of the sulfide carbon felt prepared in Example 1. The carbon felt is treated and zinc sulfide, tin sulfide and molybdenum oxide are grown thereon.
[0046] like Figure 2 A and Figure 2 As shown in b, it is a scanning electron microscope image of the lithium metal negative electrode prepared in Example 1, and the upper surface and interface of the 100 μm carbon sulfide felt and lithium metal composite compounded by roller pressing the carbon sulfide felt and lithium foil.
[0047] like Figure 3 The figure shows the X-ray diffraction pattern of the sulfide grown on the sulfide felt prepared in Example 1. The precursors used are zinc acetate, tin chloride, and ammonium molybdate. The products in the figure are ZnS, SnS2, and MoO2. In this example, molybdenum oxide is generated. When these metal salts react simultaneously, two sulfides and one oxide are generated. When ammonium molybdate is added alone, molybdenum sulfide is generated.
[0048] Example 2
[0049] (1) In a hydrothermal kettle, a mixture of 15 g / m 2 The commercial carbon felt was immersed in a mixed solution of zinc acetate and thiourea (the concentration of zinc acetate was 0.2 mol / L and the concentration of thiourea was 0.4 mol / L), and hydrothermally treated at 150°C for 12 h, cooled to room temperature, opened the hydrothermal reactor, and took out the pretreated carbon felt;
[0050] (2) The pre-treated carbon felt was rinsed with deionized water and dried at 50° C. for 16 h to obtain sulfide carbon felt;
[0051] (3) taking a lithium foil with a thickness of 50 μm and two carbon sulfide felts, covering the carbon sulfide felts on the upper and lower sides of the lithium foils respectively, and rolling them once with 2T to obtain a carbon sulfide felt and lithium metal composite with a thickness of 170 μm;
[0052] (4) The carbon sulfide felt and lithium metal complex are heated at 150°C for 24 hours to obtain a lithium metal negative electrode.
[0053] like Figure 2 Medium c and Figure 2As shown in (d), it is a scanning electron microscope image of the lithium metal negative electrode prepared in Example 2, and the upper surface and interface of the 170 μm carbon sulfide felt and lithium metal composite compounded by roller pressing the carbon sulfide felt and lithium foil.
[0054] Example 3
[0055] (1) In a hydrothermal kettle, a 20 g / m 2 The commercial carbon felt was immersed in a mixed solution of tin chloride and thioacetamide (the concentration of tin chloride was 0.5 mol / L, and the concentration of thioacetamide was 1 mol / L), and hydrothermally treated at 200°C for 5 h, cooled to room temperature, opened the hydrothermal reactor, and took out the pretreated carbon felt;
[0056] (2) The pretreated carbon felt was rinsed with deionized water and dried at 80° C. for 12 h to obtain sulfide carbon felt;
[0057] (3) taking a lithium foil with a thickness of 100 μm and two carbon sulfide felts, covering the carbon sulfide felts on the upper and lower sides of the lithium foils respectively, and rolling them twice at 3T to obtain a carbon sulfide felt and lithium metal composite with a thickness of 250 μm;
[0058] (4) The carbon sulfide felt and lithium metal complex are heated at 180°C for 3 hours to obtain a lithium metal negative electrode.
[0059] Experimental Example 1
[0060] Assembly and testing of lithium metal batteries
[0061] The battery assembled with the lithium metal negative electrode prepared in Example 1 was used as the experimental group, and the lithium foil with a thickness of 50 μm used in Example 1 was used as the control group, and button batteries and soft-pack batteries were assembled for battery performance testing. Both groups of button batteries were assembled in a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), and both groups of soft-pack batteries were assembled in a dry room (relative humidity 0.1%, dew point below -40°C, constant temperature of 25°C). The specific method is as follows:
[0062] (1) Assembly and testing of symmetrical button batteries
[0063] The experimental group used two identical lithium metal pole pieces prepared in Example 1, and the control group used two identical lithium foils, respectively, as the positive and negative electrodes of the battery (pole piece radius 4-10 mm), and PE was used as a separator to separate the two electrodes. 50 mL LS-009 electrolyte (1M LiTFSI in DME:DOL=1:1Vol%with 2%LiNO3) was injected into each button symmetrical battery. The current was 0.5-10 mA cm -2 Current density and 0.5~20mAh cm -2 Capacity charge and discharge cycles to evaluate electrochemical performance.
[0064] (2) Assembly and testing of button cell batteries
[0065] The LFP positive electrode (0.5-3 mAh cm -2 ) is paired with the lithium metal electrode or lithium foil electrode prepared in Example 1 to assemble a button full battery. The LFP-based button full battery is generally cycled in the voltage range of 2.8 to 4V, and the cycle current density can be set to 0.1 to 5C (1C = 170mAh g -1 ). Each button cell was activated for 5 cycles at a current density of 0.1C before testing.
[0066] (3) Assembly and testing of soft pack batteries
[0067] All soft-pack full batteries are assembled by semi-automatic battery production lines. The equipment and devices used include: slurry mixer, coating machine, calender, Z-type stacker and its loaded positive electrode, negative electrode and PE separator, ultrasonic welding machine and corresponding aluminum (positive electrode) and nickel (negative electrode) tabs, aluminum-plastic film packaging, heating sealing machine for aluminum-plastic film packaging, electrolyte injection and static machine, vacuum sealing machine, etc. After the battery is assembled, it is first charged at 0.1C for formation to form a stable solid electrolyte interface, and then final sealing is performed. After final sealing, long cycles are performed at 0.1C / 0.3C charge and discharge.
[0068] The soft pack battery uses the lithium metal negative electrode prepared in Example 1 or the lithium foil of the same thickness as that used in Example 1 as the negative electrode, LFP or NCM811 as the positive electrode, PE as the separator, and injects 1-4 gAh -1 The soft pack batteries were tested in a Xinwei battery cycler at 25°C, with a LFP test voltage range of 2.8-4V and a NCM811 test voltage range of 3-4.3V.
[0069] like Figure 4 As shown, the tensile stress of the lithium metal negative electrode prepared in Example 1 or the lithium foil of the same thickness as that used in Example 1 is measured. It can be seen that the strength is significantly improved after the introduction of the carbon felt.
[0070] like Figure 5 The results are shown in Table 1, which are the cycle performance test results of the button symmetrical battery assembled with the lithium metal negative electrode prepared in Example 1 or the lithium foil of the same thickness as that used in Example 1. Figure 5 It can be seen that the lithium metal negative electrode prepared in Example 1 has a smaller overpotential, stable cycle, long life, and exhibits excellent performance.
[0071] like Figure 6As shown, the thickness change trend of the soft-pack battery assembled with the lithium metal negative electrode prepared in Example 1 or the lithium foil of the same thickness as that used in Example 1 during each discharge cycle is shown. The thickness value of the first cycle is set to 1, and the ratio of each cycle to the first cycle is obtained to judge the thickening of the soft pack. For the lithium metal negative electrode prepared in Example 1, its thickness change is relatively small, and it has the ability to adapt to volume expansion.
[0072] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a lithium metal negative electrode with volume expansion adaptability, characterized in that: The following steps are involved: (1) immersing the carbon felt in a mixed solution of a metal salt and a sulfur source, performing a hydrothermal treatment, and cooling to obtain a pretreated carbon felt; (2) The pretreated carbon felt in step (1) is rinsed with deionized water and dried to obtain sulfide carbon felt; (3) taking a lithium foil and two pieces of the carbon sulfide felt described in step (2), covering the carbon sulfide felt above and below the lithium foil respectively, and rolling to obtain a carbon sulfide felt and lithium metal composite; (4) The carbon sulfide felt and the lithium metal complex described in step (3) are heated to react to obtain a lithium metal negative electrode.
2. The preparation method according to claim 1, characterized in that: In the mixed solution of the metal salt and the sulfur source in step (1), the concentration of the sulfur source is 0.01-2 mol / L, the metal salt is one or more of zinc salt, molybdenum salt or tin salt, and the sulfur source is thiourea and / or thioacetamide.
3. The preparation method according to claim 2, characterized in that: The concentration of the zinc salt is 0.01-1 mol / L, and the zinc salt is zinc acetate or zinc chloride. The concentration of the molybdenum salt is 0.01-1 mol / L, and the molybdenum salt is ammonium molybdate or molybdenum chloride. The concentration of the tin salt is 0.01-1 mol / L, and the tin salt is tin chloride.
4. The preparation method according to claim 1, characterized in that: The weight density of the carbon felt in step (1) is 5 to 30 g / m 2 .
5. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal treatment in step (1) is 130 to 200° C., and the time of the hydrothermal treatment is 5 to 48 hours.
6. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 50-100° C., and the drying time is 10-16 hours.
7. The preparation method according to claim 1, characterized in that: The thickness of the lithium foil in step (3) is 5 to 200 μm; the rolling pressure in step (3) is 0.5 to 10 T, and the number of rolling is 1 to 2 times; the thickness of the carbon sulfide felt and lithium metal composite in step (3) is 30 to 500 μm.
8. The preparation method according to claim 1, characterized in that: The temperature of the heating reaction in step (4) is 100 to 180° C., and the time of the heating reaction is 1 to 48 hours.
9. The lithium metal negative electrode prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the lithium metal negative electrode prepared by the preparation method according to any one of claims 1 to 8 or the lithium metal negative electrode according to claim 9 in preparing a lithium metal battery with adaptive volume expansion performance.
Citation Information
Patent Citations
Lithium ion battery negative electrode material and preparation method
CN107681133A
Method for preparing tin / lithium disulfide composite negative electrode through combination of melting and mechanical rolling
CN117253967A
Method for preparing porous ultrathin lithium metal negative electrode based on fiber surface infiltration and application
CN117317146A
Composite lithium metal negative electrode, preparation method therefor, and secondary lithium battery and device
WO2022000292A1
